2023
DOI: 10.1101/2023.01.27.525953
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early life exposure to broccoli sprouts confers stronger protection against enterocolitis development in an immunological mouse model of inflammatory bowel disease

Abstract: Inflammatory Bowel Diseases (IBD) are chronic conditions characterized by inflammation of the gastrointestinal tract that heavily burden daily life, result in surgery or other complications, and disrupt the gut microbiome. How IBD influences gut microbial ecology, especially biogeographic patterns of microbial location, and how the gut microbiota can use diet components and microbial metabolites to mediate disease, are still poorly understood. Many studies on diet and IBD in mice use a chemically induced ulcer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 163 publications
1
3
0
Order By: Relevance
“…Similar to the findings from in vitro studies, broccoli has been reported to have anti-inflammatory, antioxidant, and prebiotic effects against IBD in animal models ( Table 2 [ 48 , 99 , 102 , 105 , 107 , 111 , 112 , 116 , 118 , 122 , 125 , [127] , [128] , [129] , [130] , [131] , [132] , [133] , [134] , [135] , [136] , [137] , [138] , [139] , [140] , [141] ] and Figure 1 ). Both the UC and CD models use chemical triggers or genetic knockouts.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Similar to the findings from in vitro studies, broccoli has been reported to have anti-inflammatory, antioxidant, and prebiotic effects against IBD in animal models ( Table 2 [ 48 , 99 , 102 , 105 , 107 , 111 , 112 , 116 , 118 , 122 , 125 , [127] , [128] , [129] , [130] , [131] , [132] , [133] , [134] , [135] , [136] , [137] , [138] , [139] , [140] , [141] ] and Figure 1 ). Both the UC and CD models use chemical triggers or genetic knockouts.…”
Section: Discussionsupporting
confidence: 75%
“… Prebiotic, Anti-inflammatory mdr1a−/− mice [ 132 ] SFN Crude extract 4% 12 d NFkB, TNFɑ, IL10, MCP-1, and COX 2 No significance DSS-rat [ 102 ] N.R. Juice 1.5 mL 7 d IL8 Anti-inflammatory DSS mice [ 133 ] SFN, Lipids Edible nanoparticles mean diameter 32.4 nm 10 and 13 d AMPK, IL10, TNFɑ, IL17A and IFN-γ Anti-inflammatory DSS mice [ 116 ] SFN, Lipids Edible nanoparticles mean diameter 32.4 nm 10 d TNFɑ, IL6, and IL23 Anti-inflammatory Rag1−/− mice [ 116 ] Broccoli sprouts GLR, SFN Steamed and freeze-dried 10% (w/w) 34 d Bacillota, Pseudomonadota, Bacteroidota and Verrucomicrobiota; TNFɑ, IL1β and IL6 Prebiotic, Anti-inflammatory DSS mice [ 48 ] SFN, GLR Streamed 5% (w/w) 13 d microbial hydrolase, Bacillota Prebiotic DSS mice [ 105 ] SFN raw 10% (w/w) 2 wk E. coli and Helicobacter Prebiotic, Anti-inflammatory IL10-KO mice [ 134 ] Broccoli sprouts and seed GLR, Glucoiberin, Glucoerucin,...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many dietary contents have protective potential in IBD treatments, such as Spermidine, Chlorophyllin in green vegetables, steamed or raw broccoli sprouts with high levels of sulforaphane and fruits like avocado. 54 59 Spermidine, with high levels in soybeans, wheat germ, and aged cheese, has strong anti-inflammatory potential via promoting an M2-like macrophage differentiation, while it is ineffective in the macrophages of IBD patients carrying PTPN2 SNP rs1893217. 54 Mannose, exerts a potential therapeutic effect on both DSS-induced and IL-10-deficient colitis mouse models by limiting cathepsin B release from lysosomes which prevents mitochondrial dysfunction and TJs disruption.…”
Section: Disease Pathogenesismentioning
confidence: 99%
“…As a result, it exhibits progressive development of chronic enteritis without intervention, contrasting with the chemical-induced IBD model in healthy animals. Additionally, the modeling cycle for this model is notably longer than the included model (Singh et al, 2012;Holcomb et al, 2023). OVA primarily induces allergic enteritis, predominantly mediated by type I hypersensitivity through IgE (Kato et al, 2023).…”
Section: Animal Modelsmentioning
confidence: 99%